2002
DOI: 10.1046/j.1365-294x.2002.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of genetic diversity in sea otters (Enhydra lutris) associated with the fur trade of the 18th and 19th centuries

Abstract: Sea otter (Enhydra lutris) populations experienced widespread reduction and extirpation due to the fur trade of the 18th and 19th centuries. We examined genetic variation within four microsatellite markers and the mitochondrial DNA (mtDNA) d-loop in one prefur trade population and compared it to five modern populations to determine potential losses in genetic variation. While mtDNA sequence variability was low within both modern and extinct populations, analysis of microsatellite allelic data revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
3
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 26 publications
6
88
3
2
Order By: Relevance
“…Some recent studies have been conducted over short time frames, for example, within 50-200 years (e.g., ref. 30). The general focus of these studies has been to detect any changes in the overall levels of genetic variation between temporarily separated populations that were severely bottlenecked as a result of human exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have been conducted over short time frames, for example, within 50-200 years (e.g., ref. 30). The general focus of these studies has been to detect any changes in the overall levels of genetic variation between temporarily separated populations that were severely bottlenecked as a result of human exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence was threefold: (1) no significant differences were detected in mtDNA and microsatellite diversities between the historical and modern samples; (2) no significant F ST values were found between the historical and modern samples; and (3) no significant temporal changes in N e were detected between the historical and modern samples. Although mtDNA diversity shows a decreasing trend over time (Table 2) Many studies have shown that populations experiencing reductions in population size would undergo changes in genetic diversity (e.g., Groombridge et al 2000, Larson et al 2002, Paxinos et al 2002. For example, Mauritius Kestrels experienced significant loss of genetic diversity resulting from a severe population bottleneck, but have recovered from a single wild breeding pair (Jones 1987), demonstrating an unexpected resilience of the population.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that reducing the number of individuals within a species will lead to a concomitant loss of genetic diversity, as has been documented in endangered species such as Mauritius Kestrels Falco punctatus (Groombridge et al 2000), sea otters Enhydra lutris (Larson et al 2002), Hawaiian Geese Branta sandvicensis (Paxinos et al 2002), and orangutans Pongo pygmaeus ). Genetic diversity is often linked to evolutionary potential and the ability of species to respond to environmental changes (Amos and Balmford 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid and irreversible loss of genetic diversity further increases extinction risk of a species and underscores the need for preemptive conservation action. However, reduced genetic variability must be shown to be truly a recent bottleneck through anthropogenic disturbance, as in the case of sea otters being impacted by the fur trade (Larson et al 2002). In other mammalian species, such as cheetahs (MenottiRaymond and O'Brien 1993) and wolverines (Schwartz et al 2007), low genetic variability is a result of previous historical demographic changes (e.g., bottlenecking from Pleistocene glacial cycles, founder effects at periphery of distribution).…”
Section: Estimating Extinction Risk and Extinction Rate: The Role Of mentioning
confidence: 99%